2023
DOI: 10.1088/1361-6560/acbde3
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial 3D ultrasound localization microscopy using a large element matrix array with a multi-lens diffracting layer: an in vitro study

Abstract: Objective Early diagnosis and acute knowledge of cerebral disease require to map the microflows of the whole brain. Recently, ultrasound localization microscopy (ULM) was applied to map and quantify blood microflows in 2D in the brain of adult patients down to the micron scale. Whole brain 3D clinical ULM remains challenging due to the transcranial energy loss which reduces significantly the imaging sensitivity. Approach Large aperture probes with a large surface can increase both the field of view and sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…By modifying the field in this way, we more evenly sample the k -space of our imaging aperture while avoiding any symmetries that would give rise to artifacts such as grating lobes ( Fig. 1B ) ( 21 ). This more uniform sampling of k -space increases the lateral resolution of the imaging system at the expense of increased clutter/side lobes, which can be seen in the imaging performance of the bare probe versus the probe with mask (cUSi) on a numerical phantom ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…By modifying the field in this way, we more evenly sample the k -space of our imaging aperture while avoiding any symmetries that would give rise to artifacts such as grating lobes ( Fig. 1B ) ( 21 ). This more uniform sampling of k -space increases the lateral resolution of the imaging system at the expense of increased clutter/side lobes, which can be seen in the imaging performance of the bare probe versus the probe with mask (cUSi) on a numerical phantom ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of small element transducer designs is their lack of sensitivity. Instead of targeting low grating lobes in their transducer design, Favre et al demonstrated the potential for the development of a large aperture array with a large element size of 4λ in silico [36] and in vitro [37]. To combat the significantly high grating lobes caused by the use of large elements, Favre et al modeled a multi-lens diffracting layer that improved both the resolution and grating lobes of the received signal.…”
Section: Introductionmentioning
confidence: 99%